Doctors as Patients: An Interpretative Study of Two Literary Narratives - Wistrand, Jonatan (Ars Medica, 2018)
Medical practice could be described as a drama in which doctors and patients are two actors with very different roles to play. While doctoring has traditionally been regarded as a rational and reliable activity, patienthood has been characterised by compliance with, and confidence, in the medical system. However, when doctors become ill this dichotomisation of medical practice is challenged. The aim of this article is to examine how this challenge has been literary described. By interpreting one autobiographical work – A leg to stand on (1984) by Oliver Sacks – and one fictional – A Country Doctor (1919) by Franz Kafka – the phenomenon of the ailing physician is exemplified and explored through narrative analysis. In the fictional, as well as in the autobiographical, narrative the 'doctor as patient' is primarily presented as a paradox and a deviation from normality. After recovery, however, doctors’ illness experiences are regarded as a valuable resource in their continued medical practice.